The first southwest Asian record of the subfamily Microdontinae, and the description of a new species of Metadon Reemer from Iran (Diptera: Syrphidae) - Gilasian, Ebrahim; Reemer, Menno; Parchami-Araghi, Mehrdad (Zootaxa, 2015)
Metadon persicus Gilasian & Reemer sp. nov. is described, based on a single female specimen from the Zagros mountains in Iran. Morphological variation among the members of the genus Metadon Reemer and their distribution in the world are discussed. Photographs of the new species are provided. The subfamily Microdontinae represents a new taxon for southwestern Asia and the genus Metadon is reported from the western Palaearctic region for the first time.